The effectiveness of combining the keyword mnemonic with retrieval practice on L2 vocabulary learning in Taiwanese EFL classes - Chia-Hui Chiu; Chad F. Hawkins (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2023)
Previous research suggests that combining the keyword mnemonic and retrieval practice produces significant benefits for L2 vocabulary learning, but only for the receptive aspect. This study examines the effectiveness of combining the two methods for productive L2 vocabulary learning. Forty-two 8th-grade Taiwanese EFL learners participated in a four-week instructional treatment. They were divided into three groups with a similar spread of English vocabulary sizes. The learning materials consisted of 21 English words unknown to the participants and equally divided into three sets of equivalent difficulty. Three learning conditions (combined method, retrieval practice, and control) were rotated for each group so that each condition was applied to each set of words one time by one of the three groups. A productive vocabulary test was designed to measure the retention of the words at three different time points after the treatment. Repeated measures ANOVAs revealed that the combined method performed similarly to retrieval practice in the immediate and the one-week delayed posttests but significantly outperformed retrieval practice in the four-week delayed posttest. The predicted superiority of using the combined method over retrieval practice alone in the productive aspect of EFL vocabulary learning over the longer term was confirmed in the present study.